Interactive Learning Media Based on Android for Computer Programming Course - Achmad, A D; Achmad, A; Putra, Z M (IOP conference series. Materials Science and Engineering, 2020)
Computer Programming is one of the basic compulsory subjects for the electrical engineering field. This subject needs continuous practice so that it can be mastered well. This study aims to develop an interactive learning media based on Android so that students can practice anywhere. The interactive learning media for computer programming course takes in explanation of operator c++, input-output statement, program structure, data type, condition, repetition, string, and array, complemented with evaluation facility using the cosine similarity method so that the automated essay scoring feature is available. Interactive features provided in this learning media are the auto complete syntax and function in the code editor. For the evaluation used the black box testing method to test the functionally of the android application and the distribution of questionnaire to determine the response of students. The responses of student have proven that the level of practically of this interactive learning media is 87.5%.